Hadith #5031 - Sunan Abi Dawud - Abdul 'Aziz bin 'Abdullah al-Majashun عبد العزيز بن عبد الله الماجشون; Abdullah bin Dinar عبد الله بن دينار العدوي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Hilal ibn Yasar said: We were with Salim ibn Ubayd when a man from among the people sneezed and said: Peace be upon you. Salim said: And upon you and your mother. Later he said: Perhaps you found something (annoying) in what I said to you. He said: I wished you would not mention my mother with good or evil. He said: I have just said to you what the Messenger of Allah (ﷺ) said. We were in the presence of the Messenger of Allah (ﷺ) when a man from among the people sneezed, saying: Peace be upo
Grade: Da'if